Ankle and Foot Spasticity Patterns in Chronic Stroke Survivors with Abnormal Gait - Sheng Li (Toxins, 2020)
Chronic stroke survivors with spastic hemiplegia have various clinical presentations of ankle and foot muscle spasticity patterns. They are mechanical consequences of interactions between spasticity and weakness of surrounding muscles during walking. Four common ankle and foot spasticity patterns are described and discussed through sample cases. The patterns discussed are equinus, varus, equinovarus, and striatal toe deformities. Spasticity of the primary muscle(s) for each deformity is identified. However, it is emphasized that clinical presentation depends on the severity of spasticity and weakness of these muscles and their interactions. Careful and thorough clinical assessment of the ankle and foot deformities is needed to determine the primary cause of each deformity. An understanding of common ankle and foot spasticity patterns can help guide clinical assessment and selection of target spastic muscles for botulinum toxin injection or nerve block.